Drought, social agents and the construction of discourse in Andalusia - Paneque Salgado, Pilar; Vargas Molina, Jesús (Taylor & Francis, 2015)
Despite the severity of the last droughts in Spain, there has not been any significant shift in the current planning strategies, due to a significant resistance to abandoning traditional practices against this hydrological risk. To better understand the origin of this resistance, the changing role of the relevant stakeholders in the debate and the key issues, this paper is aimed at undertaking a discursive analysis of the information conveyed by the media in hydrological years 2004–2005 and 2011–2012, through the application of the software Atlas.ti.
Keywords: Cuencas hidrográficas - Gestión; Sequía; Andalusia; Discourses; Scarcity; Risk; Drought